Introduction to Traditional Chinese Medicine (Out of Print) - Chris Hafner (Association of American Medical Colleges, 2006)
Abstract This web-based tutorial seeks to educate health care students and providers about Traditional Chinese Medicine (TCM). Written and reviewed by experts drawn from the University of Minnesota Medical School and community, it meets competencies for medical and nursing education. Organized into sections, this self-study module provides definitions, a brief history, a discussion of current research and evidence, explanation of the theoretical framework underlying TCM, descriptions of treatments, information on how to partner with TCM providers, and an overview of regulation and certification. The module has interactive features, including audio and video, includes links to relevant organizations and a list of comprehensive references and concludes with a self-assessment quiz based on the learning objectives. Materials offer important information on complementary therapies, of which there is very little generally available. The online format matches well with new models of medical education that emphasize individualized learning and innovative tools. Online learning offers great flexibility to faculty and students. The authors discovered that the individual online tutorials can be used in different courses in multiple ways. Some faculty replace a reading assignment or class lecture with the online tutorial, then use class time for discussions arising from the tutorial. Other faculty use the tutorial as a resource for class projects. The tutorial is designed to allow direct access to any section, so learners can quickly find information relevant to their immediate needs.